PERJANJIAN BAGI HASIL (MARO) DALAM PEMELIHARAAN TERNAK KAMBING (STUDI DI KOTA KISARAN KABUPATEN ASAHAN) - Sastra, Putri Azzahra Febriani; Sembiring, Rosnidar; Sembiring, Idha Aprilyana (BULETIN KONSTITUSI, 2022)
The problems of this research are the form of profit sharing agreement in goat raising, the rights and obligations of the parties in goat rearing and legal protection if one party fails to default in goat rearing in Kisaran city, Asahan Regency.This study uses empirical juridical research with the object of research in Siumbut Baru Village, Kota Kisaran Timur District and Sidomukti Village, Kota Kisaran Barat District, Asahan Regency. In addition, conducting interviews with livestock owners, breeders and village officials.The results showed that the form of profit-sharing agreement in the maintenance of goats in Siumbut Baru Village, Kota Kisaran Timur District and Sidomukti Village, Kota Kisaran Barat District, Asahan Regency, was based on local customary law and was made orally. The terms and obligations of the goat owner are obliged to provide and submit 100% (one hundred percent) capital and the goat owner has the right to get his investment back from the profit-sharing business results. The rights and obligations of the goat freeman are to take good care of the goats that have been entrusted to him to be cared for and are obliged to take care of the goats entrusted to him in accordance with the agreed profit sharing agreement. The right of the freemason to receive the profits from the agreed percentage distribution in the profit sharing of goat rearing. Legal protection in the goat production sharing agreement, where the owner of the goat can claim compensation in the maintenance of the goat if the object of the agreement dies because of the farmer's intentional or negligence when raising the goat. On the other hand, the breeder cannot be sued for compensation if the goat in maintenance dies due to a disease outbreak or natural disaster (force majeure), in this case the breeder is protected by law.